The running dream - Van Draanen, Wendelin (New York : Ember, 2012)
When a school bus accident leaves sixteen-year-old Jessica an amputee, she returns to school with a prosthetic limb and her track team finds a wonderful way to help rekindle her dream of running again.
Originally published: New York : Alfred A. Knopf, 2011.
Keywords: Running -- Juvenile fiction; Amputees -- Juvenile fiction; Prosthesis -- Juvenile fiction; People with disabilities -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction